Accuracy of attenuation coefficient measurement (ACM) for hepatic steatosis: comparison with MRI proton density fat fraction (MRI-PDFF) and chemical fat analysis using multimodal liver fat phantoms - Zhaivoronok, Maksym; Dynnyk, Oleh; Deresh, Nataliya; Nosenko, Tamara; Kobyliak, Nazarii (Frontiers in Medicine, 2025)
BackgroundThe objective of this study was to evaluate the accuracy and reproducibility of real-time ultrasound steatometry using attenuation coefficient measurement (ACM) in comparison with magnetic resonance imaging proton density fat fraction (MRI-PDFF) and chemical fat analysis. Specifically, we assessed the diagnostic performance and reproducibility of ultrasound-based ACM against MRI-PDFF and laboratory fat quantification using multimodal liver fat phantoms (LFPs) with varying fat-to-water ratios.MethodsSixty LFPs with different fat concentrations were examined in two radiology centers and one chemical laboratory. Each phantom underwent three assessments: MRI-PDFF, ultrasound ACM, and laboratory-based chemical fat quantification. Correlation coefficients, intraclass correlation coefficients (ICC), receiver operating characteristic (ROC) analyses, and Bland–Altman analysis were performed to evaluate the relationships and agreement among the measurement methods.ResultsMedian values of ACM, MRI-PDFF, and laboratory fat content were 2.39 (1.87–2.84), 3.88 (2.46–7.60), and 1.24 (0.51–3.90), respectively. Strong correlations were observed between ACM and laboratory fat quantification (r = 0.878, p < 0.001) and between MRI-PDFF and laboratory analysis (r = 0.881, p < 0.001). ACM also correlated strongly with MRI-PDFF (r = 0.846, p < 0.001). The intraobserver reproducibility of ACM was excellent (ICC = 0.956, p < 0.001). AUROC values were 0.984 for ACM and 0.996 for MRI-PDFF, both indicating high diagnostic sensitivity and specificity.ConclusionsACM demonstrated strong agreement with MRI-PDFF and chemical fat analysis in LFPs, supporting its potential as a reliable, accurate, and cost-effective non-invasive technique for hepatic steatosis quantification.